PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI KELAS VIII IPS MTS AN-NUR BOBISINGO KECAMATAN GALELA UTARA - Adjam, Syarifudin; Kiha, Sitnafisa (Jurnal GeoCivic, 2024)
The purpose of this study was to determine the application of the inquiry learning model to improve students' cognitive learning outcomes in class VIII IPS material at MTs An-Nur Bobisingo, North Galela District. The design of this study is classroom action research. the subjects of this study were class VIII IPS students with a total of 19 students. This study was conducted in two cycles. The instruments used in this study were teacher activity observation sheets, student activity observation sheets, test questions for cycle I and cycle II. The results of the study showed that: The value of the post-test cycle 1 was known that there were 12 students who had not achieved individual learning completion, the percentage was 58% classically and learning outcomes in cycle II and students who obtained absorption power â‰¥ 65 totaled 16 students with a percentage of classical learning completion of 89%. This proves that the Inquiry learning model can improve student learning outcomes.